2022
DOI: 10.24198/jt.vol16n1.2
|View full text |Cite
|
Sign up to set email alerts
|

Citrus Export Performances of Southeast Asian Countries: A Comparative Analysis

Abstract: Citrus is a popular horticultural commodity worldwide, including in Southeast Asian. This study aimed to comparatively analyze export performances of citrus (limited to lime and lemon) among Southeast Asian countries (ASEAN), that are represented by the top 5 larger exporters, namely Vietnam, Thailand, Indonesia, Malaysia, and Singapore. This study applied several approaches, i.e., RCA (Revealed Comparative Advantage), ECI (Export Competitiveness Index), TSI (Trade Specialization Index), AR (Acceleration Ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A lost opportunity position is where a country's commodity exports cannot take over the export market share of the destination country, even though the demand for the product's market share increases. The condition of lost opportunity refers to a decrease in the market share of domestic products while the share of the export market increases, resulting in a loss of opportunities for export market share (Budiarto & Pratita, 2022). Pakistan's mango market position for destination countries Singapore, France, Netherlands, England, Spain and Germany is in a rising star position, with a Growth of Export Market Share (X) and Growth of Commodity Market Share (Y) positive.…”
Section: Export Product Dynamic (Epd)mentioning
confidence: 99%
“…A lost opportunity position is where a country's commodity exports cannot take over the export market share of the destination country, even though the demand for the product's market share increases. The condition of lost opportunity refers to a decrease in the market share of domestic products while the share of the export market increases, resulting in a loss of opportunities for export market share (Budiarto & Pratita, 2022). Pakistan's mango market position for destination countries Singapore, France, Netherlands, England, Spain and Germany is in a rising star position, with a Growth of Export Market Share (X) and Growth of Commodity Market Share (Y) positive.…”
Section: Export Product Dynamic (Epd)mentioning
confidence: 99%
“…The latest genomic study revealed the Southeastern Himalayan valley as citrus original site, before eventually spreading around the world by numerous human activities [3]. Southeast Asian countries (Vietnam, Thailand, and Indonesia) are citrus (lime) exporters to the world market [4] and has become the center of diversity for kaffir lime [5,6].…”
Section: Introductionmentioning
confidence: 99%